2013
DOI: 10.1007/s00705-013-1612-z
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in mice vaccinated with virus-like particles composed of the GP5 and M proteins of porcine reproductive and respiratory syndrome virus

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) induces reproductive failure in sows and respiratory problems in pigs of all ages. Live attenuated and inactivated vaccines are used on swine farms to control PRRSV. However, their protective efficacy against field strains of PRRSV remains questionable. New vaccines have been developed to improve the efficacy of these traditional vaccines. In this study, virus-like particles (VLPs) composed of the GP5 and M proteins of PRRSV were developed, and the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 59 publications
0
14
0
1
Order By: Relevance
“…In contrast, significant amounts of GP5 proteins were detected associated with intercellular nanotubes. It was reported that a GP5/M protein heterodimer of arterivirus plays an important role in viral envelope formation (37)(38)(39). GP5 and M have been proposed to be the driving force for virus budding, which may be involved in the formation of the highly curved edges of the membrane (reviewed in reference 40).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, significant amounts of GP5 proteins were detected associated with intercellular nanotubes. It was reported that a GP5/M protein heterodimer of arterivirus plays an important role in viral envelope formation (37)(38)(39). GP5 and M have been proposed to be the driving force for virus budding, which may be involved in the formation of the highly curved edges of the membrane (reviewed in reference 40).…”
Section: Discussionmentioning
confidence: 99%
“…Although GP5 fusion protein had a 23-amino-acid linear epitope deletion at the C-terminus, CvBJC3m/I-ΔGP5 still maintained the neutralization epitopes located in the middle of GP5 ectodomain [29] and is able to induce mild neutralizing antibodies in mice. This result is not surprising since it has been reported that virus-like particles composed of PRRSV GP5 and M protein were capable of eliciting neutralizing antibodies during mice immunization [30]. However, whether the phenotype observed in our mice model would be able to translate into porcine vaccine development is still questionable as PRRSV GP5-based vaccines only induce unsatisfactory neutralization antibodies and confer limited protection upon challenge [3133].…”
Section: Discussionmentioning
confidence: 62%
“…The key advantage of this recombinant protein manufacturing platform is that it can perform most of the posttranslational modifications (e.g., glycosylation, disulfide bond formation, and phosphorylation) and thus can produce biologically active proteins while offering the potential for low manufacturing costs. Moreover, insect cell expression systems have been widely used for the development of various VLP vaccines against both human and animal viruses (15,16,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%